Comparison of translabyrinthine and retrosigmoid approach for treating vestibular schwannoma: A meta-analysis - Jun, Wu; Gao, Yun-long; Yu, Hai-guang; Huang, Qing-liang; Long, Xin-quan; Liu, Guo-hua; Ting, Xu; Zhong, Xiu-ying; Zhou, Yu-fan (Clinical neurology and neurosurgery, 2020)
•To roughly evaluate the efficacy and safety between trans-labyrinthine and retrosigmoid approach for treating vestibular schwannomas patients.•Potential studies were selected from PubMed, Web of Science and Cochrane Library. Gray relevant studies were manually searched.•A total of 9 publications, involving 2429 patients, of these 2429 cases with vestibular schwannomas, 1628 were from the translabyrinthine approach group versus 801 from the retrosigmoid approach group.•The results found that the translabyrinthine approach group was associated with a higher total resection rate (OR = 0.246; P = 0.026).•We found that the translabyrinthine approach group was associated with a lower rate of tinnitus (OR = 2.687; P = 0.02) and cranial nerves deficits (OR = 2.946; P = 0.001). To date, the literature directly comparing the translabyrinthine approach and retrosigmoid approach in the operation of patients with vestibular schwannoma was limited. We aimed to evaluate postoperative complications between translabyrinthine approach and retrosigmoid approach for treating vestibular schwannoma patients. Potential publications were selected from PubMed, Web of Science and Cochrane Library. Gray relevant studies were manually searched. We set the searching time spanning from the creation date of electronic engines to February 2020. STATA version 12.0 was exerted to process the pooled data. A total of 9 literature included in the study, involving 2429 patients, hails from the Germany, USA, Canada, Italy, and France. Of these 2429 patients with vestibular schwannoma, there were 1628 cases from the translabyrinthine approach group versus 801 cases from the retrosigmoid approach group. The results demonstrated that the translabyrinthine approach group was associated with a lower rate of tinnitus (OR = 2.687; 95 %CI, 1.167−6.191; P = 0.02) and cranial nerve deficit (OR = 2.946; 95 %CI, 1.562−5.557; P = 0.001). And the translabyrinthine approach group was associated with a higher total resection rate (OR = 0.246; 95 %CI (0.071−0.848); P = 0.026). However, no statistic differences were found in the incidence of the near total (OR = 0.751; P = 0.351), subtotal resection (OR = 3.664; P = 0.109), postoperative facial nerve dysfunctions (OR, 0.763; P = 0.626), postoperative meningitis (OR = 2.7; P = 0.279), cerebrospinal fluid leak (OR = 1.225; P = 0.777), postoperative headache (OR = 1.412; P = 0.339), ophthalmic complications (OR = 0.87; P = 0.59), and vascular complications (OR = 2.501; P = 0.139). Based on current evidence, the translabyrinthine approach was associated with a higher rate of total resection and a lower rate of the tinnitus and cranial nerve deficit. But the risk of cranial nerve deficit was clearly affected by the preoperative status. And a translabyrintine approach could imply a complete sensorineural hearing loss, which contribute to the lower rate of postoperative tinnitus. Consequently, more evidence-based researches are needed to supplement this opinion.